2013
DOI: 10.1245/s10434-013-3080-9
|View full text |Cite
|
Sign up to set email alerts
|

Is it Time to Stop Checking Frozen Section Neck Margins During Pancreaticoduodenectomy?

Abstract: Positive FS margin at the pancreatic neck during PD for PDAC is associated with poor survival. Extending the neck resection after a positive FS to achieve R0 margin status does not appear to improve OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 26 publications
6
29
2
2
Order By: Relevance
“…3) Freezing of tissue often leads to adverse alterations in the specimen that may hamper the final diagnostic evaluation in permanent sections, especially considering that the focus of concern is often small and may disappear as well. 195198 …”
Section: Resultsmentioning
confidence: 99%
“…3) Freezing of tissue often leads to adverse alterations in the specimen that may hamper the final diagnostic evaluation in permanent sections, especially considering that the focus of concern is often small and may disappear as well. 195198 …”
Section: Resultsmentioning
confidence: 99%
“…This finding is in line with the previous studies indicating that frozen section analysis increases the rate of complete excision by 6.0-8.4%. 1,5,14 However, the question of whether this definite increase in the R0 excision rate actually results in an improved outcome is less straightforward. In our study there was worse survival in the R0(s) group (16 months) versus the R0(p) group (31 months); p ¼ 0.04.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this unexpected result was also found by Hernandez et al 5 Taken at face value our findings suggest that frozen section may not improve overall survival and this would be in keeping with three studies which also found no statistically significant survival difference despite their improved R0 rates. 1,5,14 An older study of patients from 1992-2006 demonstrated an improved survival in patients who underwent total pancreatectomy to achieve R0 resection compared to those who did not (and therefore had an isolated positive pancreatic neck margin). It should be noted however that both groups had poor survival (median 17.9 versus 9.7 months) and that the patients included in this study were a highly selected subgroup of all those who underwent surgery (33 and 28 out of 1579 patients who underwent PD during the same period).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few single institutional series have assessed the value of this surgical maneuver, [10][11][12][13] and results are conflicting. Of these, the neck margin is the most amenable to surgical intervention, as the surgeon can often take additional pancreatic body parenchyma in an effort to clear this margin after intraoperative frozen section (FS) analysis.…”
mentioning
confidence: 99%